Uji Aktivitas Antimikroba Ekstrak Etanol Daun Matoa (Pometia pinnata) Terhadap Enterococcus faecalis dan Helicobacter pylori - Pagarra, Halifah; Haq, Muhammad Naufal Syaiful (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2025)
This study aims to determine the antimicrobial activity of ethanol extract of matoa leaves against Enterococcus faecalis and Helicobacter pylori bacteria. This study consists of sample preparation stages, sample extraction using 70% ethanol solvent with the maceration method, antimicrobial testing using the disc diffusion method. The treatments used were 5%, 7.5%, 10%, 10% extract, positive control Chloramphenicol 30 µl, and negative control distilled water each using 3 replications. Data were analyzed with SPSS 30 using the ANOVA test and Duncan's test. The test results showed positive results that ethanol extract of matoa leaves could inhibit the growth of Enterococcus faecalis and Helicobacter pylori bacteria, possibly because it contains secondary metabolite compounds. The largest inhibition zone diameter was found in the positive control in the form of Chloramphenicol 30 ppm, an antibiotic commonly used to inhibit bacterial growth, and the smallest was found in the negative control because it was only given sterile distilled water. The largest inhibition zone diameter of matoa leaf ethanol extract was found in Enterococcus faecalis with a concentration of 10%, which was 9.35 mm but had no significant difference with the other four extract concentrations. In Helicobacter pylori, the largest inhibition zone was found at a concentration of 12.5%, which was 14.13 mm and had a significant difference with other concentrations but showed no significant difference with the positive control.